Effectiveness Analysis of Fintech on Financial Performance and Banking Sustainability - Rahmi, Febri; Masril, Salsabila Olivia (Journal of Applied Accounting and Taxation, 2025)
The development of Financial Technology (Fintech) in Indonesia is quite high, especially in banking. Ease of access and service, speed of transaction processing, simple requirements that can be fulfilled at any time and from any location, and the ability to reduce operational costs are key considerations for banks to adopt it. But behind these advantages, the usage of Fintech causes concern because it is easily hacked and can be misused for fraudulent activities. This research aims to explore and understand the effectiveness of Fintech on Financial Performance and Banking Sustainability using the Unified Theory of Acceptance and Use of Technology (UTAUT). The research utilized primary data collected from eight informants, comprising one policymaker, one implementer, and six users. Data collection techniques are observation and in-depth interviews. Data analysis includes data reduction, data presentation, and conclusion. The research results stated that the service implementation of Fintech in improving financial performance is considered effective in terms of performance expectations, business expectations, and social influence, but not yet effective in terms of facilitating conditions. The service implementation of Fintech to support service sustainability is considered effective in terms of performance expectations, social influence, and facilitating conditions, but not yet effective in terms of business expectations.